2013
DOI: 10.1371/journal.pone.0054442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SGLT2 Inhibition in Human Kidney Proximal Tubular Cells—Renoprotection in Diabetic Nephropathy?

Abstract: Sodium/glucose cotransporter 2 (SGLT2) inhibitors are oral hypoglycemic agents used to treat patients with diabetes mellitus. SGLT2 inhibitors block reabsorption of filtered glucose by inhibiting SGLT2, the primary glucose transporter in the proximal tubular cell (PTC), leading to glycosuria and lowering of serum glucose. We examined the renoprotective effects of the SGLT2 inhibitor empagliflozin to determine whether blocking glucose entry into the kidney PTCs reduced the inflammatory and fibrotic responses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
4
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(202 citation statements)
references
References 28 publications
(30 reference statements)
9
174
4
7
Order By: Relevance
“…In vitro and in vivo work has suggested that sodium glucose cotransport inhibition reduces markers of inflammation and fibrosis [18,19,[29][30][31]. Although we did not measure inflammatory markers in the present trials, future studies should assess the effect of SGLT2 inhibition on pro-inflammatory and pro-fibrotic mechanisms in diabetes and associated kidney disease.…”
Section: Discussionmentioning
confidence: 85%
“…In vitro and in vivo work has suggested that sodium glucose cotransport inhibition reduces markers of inflammation and fibrosis [18,19,[29][30][31]. Although we did not measure inflammatory markers in the present trials, future studies should assess the effect of SGLT2 inhibition on pro-inflammatory and pro-fibrotic mechanisms in diabetes and associated kidney disease.…”
Section: Discussionmentioning
confidence: 85%
“…The consequent reduction in NaCl distal delivery to the macula densa decreases tubuloglomerular feedbackmediated afferent arteriolar vasoconstriction, thereby increasing glomerular afferent-to-efferent arteriolar tone, intraglomerular ultrafiltration pressure, and glomerular filtration rate (124). Proximal tubule SGLT2 upregulation and increased NaCl reabsorption also have been documented in obesity-related CKD as a result of enhanced sympathetic activity (33,125) and TGF-b1/SMAD3 axis activation (126). By virtue of these actions, SGLT2 inhibitors synergize with renin-angiotensin-aldosterone system (RAAS) inhibitors, and their combination may confer incremental renal benefits (127).…”
Section: Targeting the Renal Tubule To Improve Ckd And Nafldmentioning
confidence: 97%
“…The increase in glucose trafficking through the proximal tubular cells, consequent of an increased transport of glucose by SGLT2, could promote inflammation and fibrosis. In immortalized human proximal tubular cells, empagliflozin reduced the glucoseinduced Toll-like receptor 2 and 4 and nuclear factor-kB expression, both wellknown mediators of inflammatory and fibrotic responses in animal models of DN (42). Thus, it is tempting to hypothesize that in patients with type 2 diabetes and tubulointerstitial lesions SGLT2 inhibitors might be particularly useful in reducing tubulointerstitial fibrosis and inflammation.…”
Section: Sglt2 Inhibitors: Experimental Datamentioning
confidence: 99%